FLOODING IMPACTS AND FARMING MOTIVATION IN ANAM COMMUNITY OF ANAMBRA STATE, NIGERIA: IMPLICATION FOR FOOD SECURITY - Njideka Rita , Chiekezie (Journal of Advance Research in Food, Agriculture and Environmental Science (ISSN 2208-2417), 2023)
Climate change projections that show an increase in the frequency and intensity of climatic hazards like flooding highlight the significance of understanding community vulnerability to extreme hydrological events. The current study looked at how farmers' motivation is impacted by flooding. Two hundred and twenty-five farmers recruited from farming communities in Anam, Anambra State, Nigeria, completed a self-report instrument to ascertain their motivations relative to continuing farming activities in the era of flooding. A cross-sectional design was employed in the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, Version 23). Simple regression was run to test the primary hypothesis that flooding would predict farmers' motivation. The analysis demonstrated a statistically significant effect of flooding concerns on the farmers' motivation F (1,223), 21.31 P< .05, with the R2 indicating the independent variable accounted for 22.3% of the variation in farmers' motivation. The present finding contributes to the agricultural literature by revealing the flooding trend as a potential determinant of farmers' low motivations and the increasing low food production.